Chandelier and interfascicular neurons in the adult mouse piriform cortex - Jorge A Larriva-Sahd (Frontiers Media S.A., 2010)
The structure of two neuron types native to the adult mouse piriform cortex (PC) is described. The first cell, termed an interfascicular neuron (IFN), lies between the axon fascicles of layer I. The IFN axon divides dichotomously and daughter fibrils run horizontally in the domain of layer Ia. The frequent apposition of the IFN axon to distal denrites of the underlying pyramidal cells suggests an en passage synaptic interaction with them. A second neuron observed in layer II, or less frequently in layer III, matched in most respects the structure of the chandelier cell described elsewhere in the neo- and archi-cortex. In the PC, chandelier cells (PC-CC) display the following peculiarities. First, the PC-CC axonal field distributes in the neuropil of layers II and III and candlesticks are in close apposition to the initial axonal segment of the pyramidal cell, although somatic interactions cannot be rule out. Second, the PC-CC ascending dendrites pierce layer I, receiving short collaterals and boutons en passage from the olfactory axons therein. The possible role of IFN´s and PC-CC and their interactions with the adjacent cells is discussed in the broad context of the cellular organization of the PC.